2017
DOI: 10.1103/physrevb.96.144427
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast hot-electron induced quenching of Tb 4f magnetic order

Abstract: Abstract:We have investigated ultrafast quenching of the Tb4f magnetic order in Co 74 Tb 26 alloys, induced by femtosecond hot-electrons pulses. The hot-electron pulses were produced in specific non-magnetic capping layers by infrared fs laser pulses. Our experimental results show that sub-picosecond dynamics of Tb4f magnetic moments can be induced by nonthermal and thermal hot-electrons. We further demonstrate that the demagnetization efficiencies of non-thermal and thermal hot electrons are similar. However,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Transport of hot electrons in non-magnetic metals is an important driver for ultrafast demagnetization of an adjacent ferromagnetic material. Although prior work emphasizes the role of ballistic transport of hot electrons in the non-magnetic metallic layer for inducing indirect excitation of the adjacent ferromagnetic layer,[25,[32][33][34] we argue that based on the results of this work, diffusive transport of electrons can be as effective as ballistic transport in terms of heat flux when lep is substantially longer than the optical absorption depth. Our work also gives a different interpretation of the results of Ferté et al[33]: the authors showed the demagnetization of CoTb occurs more slowly when CoTb is heated by a Cu/Pt/Cu trilayer than by a single Cu layer of similar thicknesses.…”
mentioning
confidence: 77%
“…Transport of hot electrons in non-magnetic metals is an important driver for ultrafast demagnetization of an adjacent ferromagnetic material. Although prior work emphasizes the role of ballistic transport of hot electrons in the non-magnetic metallic layer for inducing indirect excitation of the adjacent ferromagnetic layer,[25,[32][33][34] we argue that based on the results of this work, diffusive transport of electrons can be as effective as ballistic transport in terms of heat flux when lep is substantially longer than the optical absorption depth. Our work also gives a different interpretation of the results of Ferté et al[33]: the authors showed the demagnetization of CoTb occurs more slowly when CoTb is heated by a Cu/Pt/Cu trilayer than by a single Cu layer of similar thicknesses.…”
mentioning
confidence: 77%
“…In the present paper, we describe TR-XRMS experiments on amorphous Co-Tb thin films with magnetic stripe domains conducted at the free-electron laser FERMI. Although several femtomagnetism studies have already been performed on ferrimagnetic Co-Tb [25][26][27][28], a material system of great technological relevance for future all optical magnetic data storage [29][30][31], experiments describing the evolution of magnetic domain structures in rare earth-transition metal (RE-TM) alloys following an ultrashort optical pulse are still scarce. Recently, Fan et al performed a TR-XRMS study on Co 88 Tb 12 samples using a tabletop HHG source but their analysis remained limited to the first magnetic diffraction order at the N edge of Tb (155 eV) [32].…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, we describe tr-XRMS experiments on amorphous Co-Tb thin films with magnetic stripe domains conducted at the free-electron laser FERMI. Although several femtomagnetism studies have already been performed on ferrimagnetic Co-Tb [25][26][27][28] , a material system of great technological relevance for future all optical magnetic data storage [29][30][31] , data describing the evolution of magnetic domain structures in rare earth -transition metal (RE-TM) alloys following an ultrashort optical pulse are still scarce. Recently, Fan et al performed a first tr-XRMS study on Co 88 Tb 12 samples using a tabletop HHG source but their analysis remained limited to the first magnetic diffraction order at the N-edge of Tb (155 eV) 32 .…”
Section: Introductionmentioning
confidence: 99%